LONG-TERM CHANGES IN CHOROIDAL THICKNESS IN EYES WITH TYPE 3 MACULAR NEOVASCULARIZATION. Issue 6 (June 2021) - Kim, Jae Hui; Kim, Jong Woo; Kim, Chul Gu; Lee, Dong Won
Abstract : Purpose: To evaluate the long-term changes in subfoveal choroidal thickness (SCT) in eyes with Type 3 macular neovascularization that underwent anti–vascular endothelial growth factor therapy. Methods: This retrospective study was performed with 47 patients diagnosed with Type 3 macular neovascularization and treated with anti–vascular endothelial growth factor therapy. All the patients initially received three loading injections. The SCT was compared at diagnosis, 3 months, 12 months, and at the final follow-up visit. The velocity of changes in SCT was also compared between each period. Results: The mean follow-up period was 52.1 ± 11.0 months. The mean SCT was 143.3 ± 51.2 µ m at diagnosis, and it had significantly decreased to 128.6 ± 47.4 µ m at 3 months ( P < 0.001), 123.2 ± 45.7 µ m at 12 months ( P < 0.001), and 110.0 ± 43.0 µ m at the final follow-up ( P < 0.001). The mean velocity of the decrease in SCT was 4.9 ± 3.9 µ m per month during the first 3 months, 0.6 ± 1.2 µ m per month between the 3rd and the 12th months, and 0.3 ± 0.3 µ m per month between the 12th month and the final follow-up. The velocity of the decrease was significantly greater during the first 3 months than during the 3rd to 12th month ( P < 0.001) and 12th month to final follow-up ( P < 0.001) periods. The difference was not significant between the 3rd to 12th month and 12th months to final follow-up ( P = 0.836) periods. Conclusion: Subfoveal choroidal thickness continuously decreased over time, with a significant decrease of 23% noted in eyes with Type 3 macular neovascularization. The thickness rapidly decreased during the initial loading phase. Subsequently, a continuous but gradual decrease in the thickness was noted. Abstract : Eyes with Type 3 macular neovascularization demonstrated a remarkable decrease in choroidal thickness during the mean 52.1-month follow-up period. The thickness rapidly decreased during the initial loading phase. Subsequently, the thickness decreased more gradually.